Nutritional strategies of high level natural bodybuilders during competition preparation. Issue 1 (15th January 2018) - Chappell, A. J.; Simper, T.; Barker, M. E.
Abstract: Background: Competitive bodybuilders employ a combination of resistance training, cardiovascular exercise, calorie reduction, supplementation regimes and peaking strategies in order to lose fat mass and maintain fat free mass. Although recommendations exist for contest preparation, applied research is limited and data on the contest preparation regimes of bodybuilders are restricted to case studies or small cohorts. Moreover, the influence of different nutritional strategies on competitive outcome is unknown. Methods: Fifty-one competitors (35 male and 16 female) volunteered to take part in this project. The British Natural Bodybuilding Federation (BNBF) runs an annual national competition for high level bodybuilders; competitors must qualify by winning at a qualifying events or may be invited at the judge's discretion. Competitors are subject to stringent drug testing and have to undergo a polygraph test. Study of this cohort provides an opportunity to examine the dietary practices of high level natural bodybuilders. We report the results of a cross-sectional study of bodybuilders competing at the BNBF finals. Volunteers completed a 34-item questionnaire assessing diet at three time points. At each time point participants recorded food intake over a 24-h period in grams and/or portions. Competitors were categorised according to contest placing. A "placed" competitor finished in the top 5, and a "Non-placed" (DNP) competitor finished outside the top 5. Nutrient analysis was performed using Nutritics software. Repeated measures ANOVA and effect sizes (Cohen's d ) were used to test if nutrient intake changed over time and if placing was associated with intake. Results: Mean preparation time for a competitor was 22 ± 9 weeks. Nutrient intake of bodybuilders reflected a high-protein, high-carbohydrate, low-fat diet. Total carbohydrate, protein and fat intakes decreased over time in both male and female cohorts ( P  < 0.05). Placed male competitors had a greater carbohydrate intake at the start of contest preparation (5.1 vs 3.7 g/kg BW) than DNP competitors ( d  = 1.02, 95% CI [0.22, 1.80]). Conclusions: Greater carbohydrate intake in the placed competitors could theoretically have contributed towards greater maintenance of muscle mass during competition preparation compared to DNP competitors. These findings require corroboration, but will likely be of interest to bodybuilders and coaches.